Whole genome paired-end sequencing elucidates functional and phenotypic consequences of balanced chromosomal rearrangement in patients with developmental disorders. Issue 8 (28th March 2019) - Schluth-Bolard, Caroline; Diguet, Flavie; Chatron, Nicolas; Rollat-Farnier, Pierre-Antoine; Bardel, Claire; Afenjar, Alexandra; Amblard, Florence; Amiel, Jeanne; Blesson, Sophie; Callier, Patrick; Capri, Yline; Collignon, Patrick; et al.
Abstract : Background: Balanced chromosomal rearrangements associated with abnormal phenotype are rare events, but may be challenging for genetic counselling, since molecular characterisation of breakpoints is not performed routinely. We used next-generation sequencing to characterise breakpoints of balanced chromosomal rearrangements at the molecular level in patients with intellectual disability and/or congenital anomalies. Methods: Breakpoints were characterised by a paired-end low depth whole genome sequencing (WGS) strategy and validated by Sanger sequencing. Expression study of disrupted and neighbouring genes was performed by RT-qPCR from blood or lymphoblastoid cell line RNA. Results: Among the 55 patients included (41 reciprocal translocations, 4 inversions, 2 insertions and 8 complex chromosomal rearrangements), we were able to detect 89% of chromosomal rearrangements (49/55). Molecular signatures at the breakpoints suggested that DNA breaks arose randomly and that there was no major influence of repeated elements. Non-homologous end-joining appeared as the main mechanism of repair (55% of rearrangements). A diagnosis could be established in 22/49 patients (44.8%), 15 by gene disruption ( KANSL1, FOXP1, SPRED1, TLK2, MBD5, DMD, AUTS2, MEIS2, MEF2C, NRXN1, NFIX, SYNGAP1, GHR, ZMIZ1 ) and 7 by position effect ( DLX5, MEF2C, BCL11B, SATB2, ZMIZ1 ). In addition, 16 new candidate genes were identified. Systematic gene expression studies further supported these results. We also showed the contribution of topologically associated domain maps to WGS data interpretation. Conclusion: Paired-end WGS is a valid strategy and may be used for structural variation characterisation in a clinical setting.